2021
DOI: 10.2478/raon-2021-0048
|View full text |Cite
|
Sign up to set email alerts
|

Residual disease in lymph nodes has no influence on survival in patients with incidental gallbladder cancer – institution experience with literature review

Abstract: Background A better appreciation of the course and factors that influence incidental gallbladder cancer (iGBC) is needed to develop treatment strategies aimed to improve outcomes. The purpose of the study was to determine the influence of residual disease in the liver and lymph nodes on overall survival in re-resected patients with iGBC. Patients and methods Patients undergoing radical re-resection for iGBC from January 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In our study, it was found to be 2.6:1. The mean age was 66.4 years, similar to the literature [10]. Age >65 years was found to have a significant effect on mortality.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, it was found to be 2.6:1. The mean age was 66.4 years, similar to the literature [10]. Age >65 years was found to have a significant effect on mortality.…”
Section: Discussionsupporting
confidence: 84%
“…In recent years, the prognosis of metastatic patients has changed significantly, with longer median PFS and median OS, mainly due to the availability of systemic treatment, both adjuvant and, in particular, systemic treatment of metastatic disease with targeted drugs. 2 , 3 , 4 , 6 , 7 Specific serum biochemical tumor biomarkers are still lacking for the early detection of BTCs, and it is also difficult to distinguish them from metastatic diseases of other cancers. 3 , 4 Therefore, extensive efforts are underway to identify more precise biomarkers for the diagnosis, treatment response, and prognosis of BTCs.…”
Section: Discussionmentioning
confidence: 99%
“…The first treatment is surgery of the primary tumor, detected at an early stage in selected patients, and is the only potentially curative treatment, if radically resected (R0) without residual disease. 3 , 4 , 6 Five-year survival ranges depend on the stage of the disease and are from 9% to 25%, 10% to 15% and 15% to 35% for ICC, ECC and gallbladder carcinoma, respectively. 3 Over the last 10 years, the prognosis of patients has changed significantly, mainly due to the availability of systemic treatment, both adjuvant and, in particular, systemic treatment of metastatic disease with targeted drugs.…”
Section: Introductionmentioning
confidence: 99%
“…TME exhibits survival signals as well as pro-angiogenic factors, both of which are required for tumor development and metastasis. Biomarkers mediate interactions between tumor cells and their microenvironment, resulting in breakthroughs in the early diagnosis or prevention of metastasis [29,30]. Gallbladder cancer progresses through three stages: metaplasia of normal epithelium or less hyperplasia, dysplasia or intraepithelial neoplasia, carcinoma in situ, and invasive malignancy in around 15 years [31][32][33][34].…”
Section: Cytopathological/ Histopathological Diagnosismentioning
confidence: 99%